Features of the application of technology in the context of training in Institute of vocational education and training - Gerlyand, Tetyana (Professional Pedagogics, 2015)
The article deals with the application of technology in the context of training institutions of vocational education in modern conditions.It was revealed that the main purpose of contextual learning – formation into education student of vocational educational institution of its integrated internally motivated professional activity as a future professional.An analysis of current research on the issue and the main requirements for the implementation of learning technologies in the context of vocational education.The main approaches to technology, its principles and structural features. The content of the learning context is taken from two sources: the substantive content of the studied Sciences and content of future professional activity, presented in the form of expert business model – its functions, problems, challenges, key competencies. The content of training is given in the form of educational texts, but their information is substantive and social context of the future life and work of the student.Contextual learning – learning, professionally oriented. All the knowledge in this study are available, and only in the context of a future professional activities. The common ground of different techniques is becoming a professional context. It stressed the need for interdisciplinary and multidisciplinary relations, without which the learning context is meaningless.On the basis of acquires further development and formation of the professional development of the individual student of vocational educational institution that will contribute to more effective its entry into their future profession.
Keywords: technology; contextual learning; problem situation; integration